2021
DOI: 10.1016/j.bbih.2021.100287
|View full text |Cite
|
Sign up to set email alerts
|

Neuroinflammation in World Trade Center responders at midlife: A pilot study using [18F]-FEPPA PET imaging

Abstract: Background Neuroinflammation has long been theorized to arise from exposures to fine particulate matter and to be modulated when individuals experience chronic stress, both of which are also though to cause cognitive decline in part as a result of neuroinflammation. Objectives Hypothesizing that neuroinflammation might be linked to experiences at the World Trade Center (WTC) events, this study explored associations between glial activation and neuropsychological measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 77 publications
2
10
0
Order By: Relevance
“…Indeed, studies have documented disruptions in white matter connectivity and integrity in trauma and PTSD populations [ 119 124 ], which has been proposed to have an underlying etiology due to increased neuroinflammation due to psychosocial stress [ 125 132 ], with accelerated brain senescence [ 133 135 ], and that normal brain aging is associated with reduced cortical complexity [ 39 , 58 – 61 ]. Coupled with our own studies that have identified increased neuroinflammation in responders with chronic WTC-PTSD [ 68 , 136 138 ], we therefore propose that one possible avenue for the reduced cortical complexity observed in WTC responders with chronic PTSD in this study may be due to increased neuroinflammation from elevated psychosocial stress, which may have led to white matter atrophy, in turn leading to reduced cortical complexity through retraction of axonal tension. Future studies with WTC responders and other trauma affected populations should directly interrogate FD analysis, and if possible, integrate diffusion tensor imaging analyses of white matter integrity from MRI, along with concurrent Positron Emission Tomography (PET) biomarkers of neuroinflammation, such as the Translocator protein 18-kDa (TSPO) ligand FEPPA, or others.…”
Section: Discussionsupporting
confidence: 78%
“…Indeed, studies have documented disruptions in white matter connectivity and integrity in trauma and PTSD populations [ 119 124 ], which has been proposed to have an underlying etiology due to increased neuroinflammation due to psychosocial stress [ 125 132 ], with accelerated brain senescence [ 133 135 ], and that normal brain aging is associated with reduced cortical complexity [ 39 , 58 – 61 ]. Coupled with our own studies that have identified increased neuroinflammation in responders with chronic WTC-PTSD [ 68 , 136 138 ], we therefore propose that one possible avenue for the reduced cortical complexity observed in WTC responders with chronic PTSD in this study may be due to increased neuroinflammation from elevated psychosocial stress, which may have led to white matter atrophy, in turn leading to reduced cortical complexity through retraction of axonal tension. Future studies with WTC responders and other trauma affected populations should directly interrogate FD analysis, and if possible, integrate diffusion tensor imaging analyses of white matter integrity from MRI, along with concurrent Positron Emission Tomography (PET) biomarkers of neuroinflammation, such as the Translocator protein 18-kDa (TSPO) ligand FEPPA, or others.…”
Section: Discussionsupporting
confidence: 78%
“…Previous work using neuroimaging in the WTC population has found that cognitively impaired responders with PTSD are indistinguishable in levels of cortical, 39 cerebellar, 40 and hippocampal atrophy 41 when compared with cognitively impaired responders without PTSD. However, one study of MCI noted that glial activation was related to PTSD symptom severity, 42 whereas other studies noted the presence of proteins consistent with interneuronal neurodegeneration 43 and amyloidogenesis. 44 In a neuroimaging study of cortical complexity, 45 a measure of concurrent cortical thickness, neural density, and surface convolution previously demonstrated to be negatively associated with psychiatric disorders, we demonstrated reduced fractal dimensions in WTC responders with PTSD vs those without.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they have genetically analyzed postmortem brain samples from female PTSD patients and found reduced expression of the microglial-related genes TNFRSF14 and TSPOAP1 in addition to TSPO in the prefrontal cortex [26]. Conversely, Deri et al reported in a similar PET study that the severity of PTSD symptoms was positively correlated with TSPO expression in the hippocampus and prefrontal cortex [27]. We summarize animal, PET, and postmortem studies in Table 1.…”
Section: Microglia and Ptsdmentioning
confidence: 99%